Measuring Changes in Farmers' Attitudes to Agricultural Cooperatives: Evidence from Swedish Agriculture 1993–2013. Issue 4 (2nd March 2016) - Hakelius, Karin; Hansson, Helena
ABSTRACT: This study assessed changes in farmers' attitudes to agricultural cooperatives by developing a behavioral framework based in psychological and psychometric theory for measuring attitude change. The assessment focused on a unique dataset that allowed attitude coverage and strength of evaluation derived from data collected in 1993 and in 2013 to be evaluated. Explorative factor analytical methods revealed the attitude construct to be two‐dimensional in both datasets, covering the domains named " Commitment " and " Trust " in both cases. Thus, the coverage of the attitude construct seemed unchanged. However, the strength of evaluation of both attitude dimensions was significantly increased. These findings have clear policy implications for agricultural cooperatives, since understanding the nature of changes in attitudes to these organizations is important for their successful development. [EconLit citations: P13; Q13].